Effects of delta-tocotrienol supplementation on glycaemic control in individuals with prediabetes — a randomized controlled study - Farhana Suleman; Dilshad Ahmed Khan; Muhammad Amjad Pervez; Mohammad Aamir (Journal of the Pakistan Medical Association, 2022)
Objective: To study the effects of delta-tocotrienol on glycaemic control parameters in individuals with pre-diabetes. Method: The randomised control trial was conducted at the Armed Forces Institute of Pathology, Rawalpindi, Pakistan, from July 15 to November 15, 2019, and comprised individuals aged 18-60 years having fasting plasma glucose of 5.6 to 6.9mmol/L or glycosylated haemoglobin of 5.7 to 6.4%. They were randomised into group A receiving 300mg delta-tocotrienol and group B receiving a placebo once daily for 12 weeks. Weight, height, waist circumference, fasting plasma glucose, insulin and glycosylated haemoglobin were measured at the beginning and end of the trial to assess any change. Body mass index and homeostatic model assessment-insulin resistance were also calculated. Data was analysed using SPSS 21. Results: Of the 77participants, 40(52%) were in group A and 37(48%) in group B. Group A showed significantly greater reduction in terms of fasting plasma glucose, glycosylated haemoglobin, insulin and homeostatic model assessment-insulin resistance index (p?0.001) post-intervention. Conclusion: Delta-tocotrienol supplementation was found to have a significant effect in improving glycaemic control parameters in persons with pre-diabetes. Futures larger scale clinical trials are needed to confirm these findings. Continuous...